Creating playful urban interiors through community-based traditional games (Department of Architecture Faculty of Engineering Universitas Indonesia, 2025)
This paper explores the design process of the 'magic circle' as a form of a playful urban interior, inspired by traditional games as a form of ludic or play activity. Traditional games reflect the intersection of culture and social activities, offering elements and rules adaptable to create an inclusive and creative public interior. The research analyses the process and spatialities of traditional games, mapping common play areas, frequently encountered games, and how communities preserve these traditions in an urban context. This paper explores such spatialities in the play-event conducted by the Hong community, an urban community focusing on the preservation of traditional games in Bandung, West Java. The study investigates how traditional games in this event enable the creation of a playful space as a form of urban interior interventions. Based on such reading, the study proposes a playful interior system, consisting of ludic, crafting, and immersive space types. This system expands the design methodologies of the public interior, allowing user participation and flexibility in the playful inhabitation of the urban context.